Sources of seasonal wetland methane emissions in permafrost regions of the Qinghai-Tibet Plateau - Zhang, Shunyao; Zhang, Fugui; Shi, Zeming; Qin, Aihua; Wang, Huiyan; Sun, Zhongjun; Yang, Zhibin; Zhu, Youhai; Pang, Shouji; Wang, Pingkang (Scientific Reports, 2020)
Abstract In this study, systematic soil methane cycle geochemical monitoring was carried out in a typical gas hydrate region in the Qinghai-Tibet Plateau. Soil gas samples were collected for hydrocarbon components and carbon isotope analysis. Meanwhile, soil-methane fluxes from the upper active layer (20–30 cm) were monitored during six months of one year. The results of this research provide evidence of a new source of methane emission from wetland soils in permafrost regions: gas hydrate release. Sites with large methane emissions were found using flux monitoring, the characteristics of thermogenic methane were identified using carbon isotope tracing, and the relationship between emission by soils and effusion from gas hydrates was determined through correlation analyses of soil-adsorbed hydrocarbons. Seasonal variation of methane emissions are also discussed by considering the emission of bacterial methane, thermogenic methane, and the absorption of methane from the soil active layer. These comprehensive findings provide valuable information for carbon cycle research of wetlands in permafrost regions.